2016
DOI: 10.1016/j.ygyno.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia and its association with survival in patients with locally advanced cervical cancer

Abstract: Objective To evaluate the association between lymphopenia and survival in women with cervical cancer treated with primary chemoradiation. Methods A single institution, retrospective analysis of patients with stage IB2-IVA cervical cancer who received upfront chemoradiation from 1998 to 2013 was performed. Complete blood counts from pre-treatment to 36 months post-treatment were analyzed. Lymphopenia and known prognostic factors were evaluated for an association with progression-free (PFS) and overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 32 publications
7
114
0
Order By: Relevance
“…In addition, the authors reported a significant decline in TLC, with values lower than 500/KL in 29 (73%) of 40 patients. Similarly, Wu et al 15 reported severe lymphopenia (TLC G500 cells/KL) in 53% of patients. In the current study, posttreatment lymphopenia was observed in 61% of patients.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In addition, the authors reported a significant decline in TLC, with values lower than 500/KL in 29 (73%) of 40 patients. Similarly, Wu et al 15 reported severe lymphopenia (TLC G500 cells/KL) in 53% of patients. In the current study, posttreatment lymphopenia was observed in 61% of patients.…”
Section: Discussionmentioning
confidence: 80%
“…Although we found that OS and DFS were inferior for patients with pretreatment lymphopenia compared with those without, on multivariate analysis, posttreatment lymphopenia had no significant impact on OS and DFS, similar to previous findings. 15 The present study had clear limitations, primarily because of its retrospective nature. In addition, newer marrow-sparing irradiation techniques will be better to assess the effect of tumor-related posttreatment lymphopenia, not radiation-induced lymphopenia.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[1619] Furthermore, Wu et al suggested that pre- and post-treatment lymphopenia might be associated with deceased survival in patients with cervical cancer. [20] …”
Section: Discussionmentioning
confidence: 99%